2017
DOI: 10.1007/978-94-024-1079-2_3
|View full text |Cite
|
Sign up to set email alerts
|

Taurine Supplementation Reduces Renal Nerve Activity in Male Rats in which Renal Nerve Activity was Increased by a High Sugar Diet

Abstract: This study tests the hypothesis that taurine supplementation reduces sugar-induced increases in renal sympathetic nerve activity related to renin release in adult male rats. After weaning, male rats were fed normal rat chow and drank water containing 5% glucose (CG) or water alone (CW) throughout the experiment. At 6-7 weeks of age, each group was supplemented with or without 3% taurine in drinking water until the end of experiment. At 7-8 weeks of age, blood chemistry and renal nerve activity were measured in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…The authors theorized that Taurine would attenuate the CAF stimulus on ANS. This proposition is supported by Rakmanee et al 48 , which evaluated the effects of taurine on autonomic nervous system in adult male rats. As a main finding, they reported that taurine supplementation decreased sympathetic renal nerve activity in animals with high sugar diet.…”
Section: Caf Combined With Supplementsmentioning
confidence: 65%
“…The authors theorized that Taurine would attenuate the CAF stimulus on ANS. This proposition is supported by Rakmanee et al 48 , which evaluated the effects of taurine on autonomic nervous system in adult male rats. As a main finding, they reported that taurine supplementation decreased sympathetic renal nerve activity in animals with high sugar diet.…”
Section: Caf Combined With Supplementsmentioning
confidence: 65%